2001
DOI: 10.1103/physrevd.63.103509
|View full text |Cite
|
Sign up to set email alerts
|

Affinity for scalar fields to dissipate

Abstract: The zero temperature effective equation of motion is derived for a scalar field interacting with other fields. For a broad range of cases, involving interaction with as few as one or two fields, dissipative regimes are found for the scalar field system. The zero temperature limit constitutes a baseline effect that will be prevalent in any general statistical state. Thus, the results found here provide strong evidence that dissipation is the norm not exception for an interacting scalar field system. For applica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
240
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 116 publications
(254 citation statements)
references
References 46 publications
14
240
0
Order By: Relevance
“…The results obtained in Ref. [21] show that we can evade the assumption of an initial high temperature thermal bath as used in Ref. [28] to derive the local equations of motion for the fields and makes it, therefore, more appropriate to the application we intend for here, which is the study of the initial conditions problem for the onset of inflation in hybrid inflation models characterized by potentials like Eq.…”
Section: The Model and Its Propertiesmentioning
confidence: 99%
See 4 more Smart Citations
“…The results obtained in Ref. [21] show that we can evade the assumption of an initial high temperature thermal bath as used in Ref. [28] to derive the local equations of motion for the fields and makes it, therefore, more appropriate to the application we intend for here, which is the study of the initial conditions problem for the onset of inflation in hybrid inflation models characterized by potentials like Eq.…”
Section: The Model and Its Propertiesmentioning
confidence: 99%
“…In Ref. [21] we have studied in details the general equations for the non-Markovian dissipative kernels at zero temperature and shown that for a certain class of field decaying modes the Markovian approximation is also a valid assumption. The results obtained in Ref.…”
Section: The Model and Its Propertiesmentioning
confidence: 99%
See 3 more Smart Citations